Proceso administrativo de restablecimiento de los derechos de los niños / Eficacia del proceso administrativo de restablecimiento de derechos de los niños (2017)
Having regard to the principle of the best interest of the child guaranteed by political constitution of Colombia of 1991 and the current code of childhood and adolescence, children are subjects of special protection; therefore the state as guarantor of them develops the administrative process of re-establishment of their rights which aims to generate measures that safeguard the children’s integrity, even more when they are in situations where their fundamental rights are being violated. In view of the foregoing this work intends to analize how do you get the administrative process of re-establishment of the children’s rights, considering the current situation of the country regarding the scourge of violation of their rights and from the perspective of the High Courts, who from their sentences have established jurisprudential guidelines for the fulfilment of that process by the commissioned officials, in order to identify if this is effective or not.